The Myth of Median Nerve in Forearm and Its Role in Double Crush Syndrome: A Cadaveric Study - Abdalbary, Sahar A.; Abdel-Wahed, Mohamed; Amr, Sherif; Mahmoud, Mostafa; El-Shaarawy, Ehab A. A.; Salaheldin, Safinaz; Fares, Amal (Frontiers in Surgery, 2021)
Abstract Purpose This study aims to histologically compare the median nerve in the arm, forearm, and wrist, to help understand how cervical radiculopathy in a double crush phenomena causes distal nerve dysfunction at the carpal tunnel and median nerve with concurrent absence of symptoms at the forearm. Methods The study was performed on 12 fresh cadaveric upper limbs free from any injury or operation. Male cadavers with an age range of 35–40 years were used. The dissection of the median nerve and the histological examinations of the specimens from the arm, forearm, and wrist were conducted to evaluate variations in the epineurium thickness (µm), perineurium thickness (µm), number of fascicles per nerve trunk, area percent of myelin covering, and area percent of neurolemmal sheath. Results Morphometric and statistical results of the cadaveric median nerve trunk revealed that the mean epineurium and perineurium thickness measured in H&E-stained sections in the forearm were significantly greater than those in the arm and wrist specimens. Further, the mean percent area of the myelin covering in the forearm was significantly lower than that in the arm and wrist specimens in osmium oxide stained sections (p < 0.001). There were, however, no significant differences in the neurolemmal sheath among the arm, forearm, and wrist specimens in the silver stained sections. Conclusion The histological differences explained the high concomitant occurrence of CTS and cervical radiculopathy and concurrent absence of symptoms at the forearm . Hence, we suggest cautious evaluation of patients with upper limb symptoms, since the management of these conditions are quite different.